L’émergence d’une sexualité juvénile hors mariage chez les jeunes de Sidi Ifni (Maroc) - Leila Boufraioua (L’Année du Maghreb)
Among the young people of Sidi Ifni, the evolution of mentalities have evolved that has been progressively modifying the modes of entry into adulthood. As a result of these evolutions, early marriages have disappeared, and the prolongation lengthening of the education schooling offers to the youth a free time of maturation outside of the conjugal sphere. Access to adult status is granted only in exchange forafter a long period of waiting, a period during which the Ifnaouis explore affective relationships already, right from during the secondary and college or high school’s times. However, dating relationships are becoming a new stage for them to understand the mechanisms that leading to the decline of celibacy and to the rise of sexual relations outside marriage. According to the survey, 50% of men who married between the ages of 20 and 24 reported having had premarital sexuality with their future spouse. In this context, sexuality outside marriage is often associated with the idea of eventually creating a family with a partner. This view is also shared by women, with one-quarter of married women in the 30-35 age group claiming to have begun sexual relationships with their fiancé long before marriage. Thus, in spite of moral prohibitions, dating relationships are thus trivialized and the influence of the outside world is callings into question the puritan education. More and more young people are transgressing the laws of social morality. and schools is are becoming the places where boys and girls are initiated into romantic relationships.; therefore, the gateway to sexuality outside marriage is therefore being opened. In Sidi Ifni, these socio-cultural evolutions have deeply undermined patriarchal family structures, matrimonial institutions and gender relations.